Effect of Preservice Classroom Management Training on Attitudes and Skills for Teaching Children With Emotional and Behavioral Problems: A Randomized Control Trial. (February 2019) - Klopfer, Kristina M.; Scott, Katreena; Jenkins, Jennifer; Ducharme, Joe
Childhood emotional and behavioral problems are prevalent in elementary classroom settings, making it imperative that high-quality, efficacious training be available to support teachers in managing disruptive and distressed child behaviors. Our study used a randomized control design to examine the impact of 36 hours of preservice education targeted at improving the attitudes of teachers toward children with emotional and behavioral difficulties, and developing their skills in using proactive and preventative strategies to address anticipated behavioral challenges. Eighty-two preservice teachers were randomly assigned to an elective course on management of emotional and behavioral problems (50 teachers) or to an alternate elective of their choice (32 teachers). Results highlight the positive influence of targeted preservice instruction; specifically, there were medium to large posttest effect size differences between preservice teachers who received this elective as compared with those who did not on measures of teachers' use of psychological pressure (e.g., teacher disappointment and shaming; d = 0.76), their positive emotions ( d = 0.69), negative reactions ( d = 1.05), and their use of proactive strategies ( d = 1.43 and 1.59), inadequate strategies ( d = 0.73), and reactive strategies ( d = 1.01) in response to challenging child behaviors in simulated classrooms. No significant intervention-related differences were noted in preservice teacher self-efficacy, endorsement of rules and control, warmth and support, or negative beliefs. Overall, results provide promising evidence that preservice training can effectively affect the immediate attitudes and skills of teachers for supporting children with emotional and behavioral problems in a regular classroom context.